Langfuhr Taubenweg / Photogr. Franz Arndt. - Arndt, Franz (Photogr. und Verlag Franz Arndt, 1900)
Przedstawia ulicę Władysława Pniewskiego (niem. Taubenweg) w Gdańsku Wrzeszczu, widok ze skrzyżowania z ul. Jaśkowa Dolina, ok. 1900 r.